1956
DOI: 10.1084/jem.103.1.87
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of Virulent and Avirulent Staphylococci in the Tissues of Normal Mice

Abstract: The experiments to be described in this and the following two papers are part of an attempt to investigate the effect of metabolic and physiologic disturbances on resistance to bacterial infections. One of the models used in our laboratory for this purpose being the experimental infection of mice with staphylococci, it proved necessary to acquire as a background more precise information concerning the natural history of this experimental disease in normal animals.While not designed for the purpose of analyzing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

1960
1960
1999
1999

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(28 citation statements)
references
References 12 publications
3
25
0
Order By: Relevance
“…One possible explanation for this discrepancy might be an even higher rate of albumin leakage from the circulation during acute infection. In the later stages of intravenous staphylococcal infections, most of the viable organisms recoverable from the tissues of mice are found in the kidney and numerous abscesses occur in this organ (21). It has also been observed that urinary protein increased significantly during staphylococcal infections in mice (22).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for this discrepancy might be an even higher rate of albumin leakage from the circulation during acute infection. In the later stages of intravenous staphylococcal infections, most of the viable organisms recoverable from the tissues of mice are found in the kidney and numerous abscesses occur in this organ (21). It has also been observed that urinary protein increased significantly during staphylococcal infections in mice (22).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous studies of the pathogenicity of staphylococci for mice. Experimental models employing staphylococci in mice require either the intravenous injection of at least 10 6 organisms or intraperitoneal injection with the supplementary use of mucin before progressive infection occurs (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…These strains were those used extensively by Cohn and Morse and were kindly supplied by these investigators. They are characterized below:--Sm~h Strain.--This strain of Staphylococcus aureus was isolated in 1930 from a human case of osteomyelitis and has been maintained in the laboratory of Dr. Ren~ J. Dubos because of its consistent pathogenicity for mice (5). This strain was coagulase-positive, produced yellow pigment and hemolysins, fermented mannite, and was lysed by bacteriophages 44A and 42E.…”
Section: Methodsmentioning
confidence: 99%